Internuclear Ophthalmoplegia with Ipsilateral Abduction Deficit : Half and Half Syndrome - Ulfah Rimayanti; Yunita Yunita; Batari T Umar (Majalah Oftalmologi Indonesia, 2020)
Introduction: Head trauma can often result in the complaint of diplopia. Internuclear ophthalmoplegia (INO) coexists with abduction deficit, introduced as half and half syndrome, is rarely reported. This article presents an INO case with ipsilateral abduction deficit after a head trauma. Methods: A 17-year-old male came with binocular diplopia on horizontal gaze 2 days after a head trauma. Best corrected visual acuity on both eyes was 6/6. Adduction deficit of contralateral gaze appeared in the right eye associated with an abducting dissociated horizontal nystagmus in the left eye. He also had a moderate under-action of abduction on ipsilateral gaze in the right eye. On up gaze, both eyes were found to have vertical nystagmus. Anterior and posterior segments revealed normal, except minimal chemosis on the right eye, no relative afferent pupillary defect. Brain imaging showed lesions in pons mainly on the right side. Results: Improvement of ocular movement was observed in 2 weeks. Diplopia and mild ocular movement limitation were still found after 6 months. Conclusion: Based on ophthalmologic and systemic examinations the patient had internuclear ophthalmoplegia (half) with ipsilateral abduction deficit (half): half and half syndrome. Head trauma is one of the risk factors of ocular motility disorders.